Genetic relationship among reproductive traits in Nellore cattle - Guarini, Aline Rocha [UNESP]; Neves, Haroldo Henrique de Rezende [UNESP]; Schenkel, Flávio Schramm; Carvalheiro, Roberto [UNESP]; Oliveira, João Ademir [UNESP]; Queiroz, Sandra Aidar de [UNESP] (Cambridge Univ Press, 2015)
In order to achieve improvements in production efficiency in livestock, herds of high sexual precocity and good fertility are needed. These traits increase the availability of animals in herd, either for sale or selection, allowing both greater selective intensity and greater genetic progress. This study aimed at estimating genetic parameters for reproductive traits measured directly in females in order to verify whether they could be used as selection criteria for genetic improvement in Nellore cows, as well as estimating the genetic relationship among these traits and scrotal circumference (SC), the traditional selection criterion for sexual precocity in cattle. In addition to SC, stayability (STAY), number of calvings at 53 months (NC53) and heifers rebreeding (HR) were studied. The (co)variances and genetic parameters were estimated using Bayesian inference. STAY, NC53 and HR were analyzed assuming a threshold model, whereas SC was analyzed with a linear model. Heritability estimated for NC53 was 0.22, and this trait was strongly and positively correlated with STAY, meaning selection for NC53 would improve productive longevity of Nellore cows. Correlations estimated between HR and STAY (approximate to 0.97) and between HR and NC53 (approximate to 0.99) allow an improvement on HR rates if selection was applied to traits related to longevity. Genetic correlations among SC and female reproductive traits were positive but weak, suggesting the need to use reproductive traits directly measured in females in order to obtain greater improvements in sexual precocity and longevity.
Keywords: Bayesian inference; Beef cattle; Heritability; Reproductive efficiency; Threshold model